CARD9 deficiency predisposing chromoblastomycosis: A case report and comparative transcriptome study - Huang, Chen; Deng, Weiwei; Zhang, Yi; Zhang, Kai; Ma, Yubo; Song, Yinggai; Wan, Zhe; Wang, Xiaowen; Li, Ruoyu (Frontiers in Immunology, 2022)
CARD9 mutations are known to predispose patients to phaeohyphomycosis caused by different dematiaceous fungal species. In this study, we report for the first time a patient of chromoblastomycosis caused by Phialophora expanda harboring the CARD9 mutation. Through a series of in vivo and in vitro studies, especially a comparative transcriptome study, we compared this case with our former patient suffering from phaeohyphomycosis caused by Phialophora americana. We showed that P. expanda is prone to forming sclerotic bodies both in vitro and in Card9 knockout mice, and has a stronger immunogenicity than P. americana. These data preliminary demonstrated that besides host defense, fungal specificity also contributed to the clinical phenotype in CARD9 deficient patients with dematiaceous fungal infections.